2016
DOI: 10.1002/jsfa.7685
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oregano essential oil on microbial load and sensory attributes of dried meat

Abstract: A value-added dried meat product obtained by using OEO to enhance food safety received an acceptable sensory response from consumers. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
1
22
1
3
Order By: Relevance
“…In terms of chewiness there was no significant difference between the samples. Interestingly, the mean values lead to the conclusion that the application of essential oil is not linked to easy chewiness (Table ) which is in agreement with results from our previous study in samples treated with HAB 1.5 mL and lower doses (Hernández et al, ). Ensuring chewiness is one of the most critical sensory quality criteria in jerky type snack foods (Konieczny, Stangierski, & Kijowski, ) and in the relation to the results of this study limited the consumer acceptability in terms of general liking of the texture for SB 1.5 mL treated samples which were significantly less pleasantness ( p < .05) in comparison to HAB 3, OT 1.5, and OT 3 mL treated samples (Table ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of chewiness there was no significant difference between the samples. Interestingly, the mean values lead to the conclusion that the application of essential oil is not linked to easy chewiness (Table ) which is in agreement with results from our previous study in samples treated with HAB 1.5 mL and lower doses (Hernández et al, ). Ensuring chewiness is one of the most critical sensory quality criteria in jerky type snack foods (Konieczny, Stangierski, & Kijowski, ) and in the relation to the results of this study limited the consumer acceptability in terms of general liking of the texture for SB 1.5 mL treated samples which were significantly less pleasantness ( p < .05) in comparison to HAB 3, OT 1.5, and OT 3 mL treated samples (Table ).…”
Section: Resultssupporting
confidence: 90%
“…Nowadays, oregano ( Origanum vulgare ), a herb of the Lamiaceae family, has been known as a flavoring agent as well as a very effective safe additive for meat (Govaris et al, ). Currently, there is a new study about the use of essential oils in terms of food safety during the meat drying process (Hernández et al, ); however, there is no evidence of research about the use of modified blanching treatments, in combination with essentials oils before the drying procedure and the effect on the drying behavior of the product. There are some studies analysing the effect of blanching and dipping methods, particularly, in the drying kinetics of vegetables (Afolabi, Tunde‐Akintunde, & Adeyanju, ; Cheng, Fang, & Ruan, ; Ismail, Figen, & Pişkin, 2015; Tunde‐Akintunde, Afolabi, & Akintunde, ) but to date, there have been no published studies comparing the effects of modified blanching treatments combined with the application of essential oils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of studies where OEO has been added to preserve meat products. Levels of 0.002% (20 ppm) OEO have been included in the formulation of chicken meat (Al‐Hijazeen, Mendonca, Lee, & Ahn, ), 0.005% (50 ppm) in dry cured sausages (García‐Díez et al, ), 0.05% to 2% in poultry fillets (Kahraman et al, ), 10 to 100 ppm in Italian salami (Cenci et al, ), 0.25% (v/v) in poultry sausages (El Adab & Hassouna, ), 0.345% to 3.45% in fresh sausages (Busatta, Mossi, Rodrigues, Cansian, & Oliveira, ), 2% and 4% in packaged pork (Paparella et al, ), 5% in Cypriot samarella (Ulusoy et al, ), 0.5 to 2.0% w/v in broiler breast (Chaleshtori & Chaleshtori, ), and 1.5 to 6 ml in dried meat (Hernández et al, ). These reports showed that concentrations of OEO lower than 1% were successful to inhibit microbial growth without affecting the sensory quality of the products.…”
Section: Resultsmentioning
confidence: 99%
“…OEO is recognized as safer additives for meat. Its components such as carvacrol, p‐cymene, and thymol, the three main phenols that constitute about 72.6% of MO are responsible of its antimicrobial properties (Hernández et al, ). OEO is considered as a technologically viable alternative in fine paste meat products since it improves their acceptance, confers antioxidant effect, reduces microbial growth, and have a beneficial effect on human health (Viuda‐Martos, Ruiz‐Navajas, Fernández‐López, & Pérez‐Álvarez, ).…”
Section: Introductionmentioning
confidence: 99%